2017
DOI: 10.1007/s40093-017-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the onion residue compost as an organic fertilizer in a vegetable culture in the Lower Valley of the Rio Negro

Abstract: Purpose Farming production in the lower part of Río Negro Valley (Argentina) has increased considerably during recent years, causing soil degradation and, specifically, decreasing the organic matter contents. This fact requires recovery measures, as organic amendments for soils, to improve its quality. The marked objectives for the present research is to evaluate compost as organic fertilizer, based on a mix of onion waste and bovine manure. Methods The experiment was carried out in a completely randomized des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
3
31
0
3
Order By: Relevance
“…This amount did not differ compared with other treatments with CM, different rates, and different application methods. This finding is relevant to that of Pellejero et al (2017) on lettuce, in which treatments with higher compost dosage showed higher root dry weight as well. This also included treatments with other fertilizers with high rate and broadcast application.…”
Section: Resultssupporting
confidence: 53%
“…This amount did not differ compared with other treatments with CM, different rates, and different application methods. This finding is relevant to that of Pellejero et al (2017) on lettuce, in which treatments with higher compost dosage showed higher root dry weight as well. This also included treatments with other fertilizers with high rate and broadcast application.…”
Section: Resultssupporting
confidence: 53%
“…This practice has been widely used in many countries with benefits for soil physicochemical and biological properties, increasing fertility and higher nutrient availability such as nitrogen (N), phosphorus (P), potassium. (K), calcium (Ca), and iron (Fe) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The intensive use of soil, specifically those focused on vegetable production, causes a reduction in organic material and nutrients and has been identified as one of the most important threats to its quality [13]. Thus, the purpose of this study was to evaluate the influence of organic fertilizers produced from vegetable residues on Crespa lettuce cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…O conjunto de fatores (teor de água, compostos orgânicos e compostos antioxidantes, influenciaram na resposta positiva do solo adicionado de FFH 3% quando comparados ao solo sem adição de fertilizante natural. O alto teor de umidade, alta CRa do solo adicionado de FCC, sugerem alta complexidade dos biopolímeros deste fertilizante não permitindo crescimento das folhas de alface mesmo apresentando alta atividade microbiana, quando comparado ao solo sem adição de conservantes (Pellejero, Miglierina, Aschkar, Turcato, & Jiménez-Ballesta, 2017) .…”
Section: Análise Do Solounclassified